Implementation of the Standard Inpatient Class Policy at RSUP Dr. Tadjuddin Makassar - Muhammad Alwy Arifin; Andi Luthfiyyah Anna; Dian Saputra Marzuki; Sukri Palutturi; Ryryn Suryaman Prana Putra (Journal of Public Health and Pharmacy, 2024)
Background: Based on Presidential Regulation No. 59 of 2024, which replaces Presidential Regulation No. 82 of 2018 on Health Insurance, the implementation of the Standard Inpatient Class (KRIS) is mandated for four types of hospitals in Indonesia, including RSUP Dr. Tadjuddin Chalid Makassar. The KRIS policy must be implemented in all hospitals in Indonesia cooperating with BPJS Health by June 30, 2025. However, the current implementation of KRIS primarily focuses on adjusting medical facilities and infrastructure toward a single class. To analyze the implementation of the KRIS policy at RSUP Dr. Tadjuddin Chalid Makassar in 2024 based on Input and Process aspects. Method: This study employed descriptive research with a qualitative approach, using interviews, observations, and document reviews conducted from February to March 2024 at RSUP Dr. Tadjuddin Chalid Makassar. Eleven informants were selected using purposive sampling. Result: The "Man" input is adequate but faces obstacles. There is no specific budget allocation ("Money") and no difference in financial management before and after policy implementation. "Material" needs are not fully met, and there are established "Methods" or rules for implementing the KRIS policy. Conclusion: Overall, the implementation of KRIS at RSUP Dr. Tadjuddin Chalid Makassar, as a pilot hospital for KRIS, has been successful. However, several variables still need improvement. It is recommended that the hospital enhance its strategies in various aspects of KRIS policy implementation.